Too old for technology?: age stereotypes and technology use by older adults - Mariano, João Miguel Lourenço de Oliveira (2022)
Older adults are less likely to use information and communication technologies, limiting their ability to live independently in an increasingly digital world. Despite being stereotyped as lacking technological competence, the influence of age stereotypes on older adults’ use behaviours remains largely understudied. This work aimed to investigate whether and how age stereotypes determine technology use in late adulthood. According to stereotype threat theory, the fear of confirming negative stereotypes about their age group may lead older adults to avoid using technology. Across three studies based on longitudinal and cross-sectional designs, higher levels of stereotype threat were associated with lower rates of technology use. In line with the technology acceptance model, this relationship was mediated by anxiety, perceived ease of use, perceived usefulness, and behavioural intention. In turn, as implied by stereotype embodiment theory, the internalization of age stereotypes endorsed earlier in life into self-perceptions of ageing later in life may deter older adults from using technology. Across three studies based on longitudinal data from the Health and Retirement Study and the German Ageing Survey, more positive self-perceptions of ageing were associated with higher levels of technology use. Cognitive functioning mediated this relationship. By confirming the assumptions of both theories, these findings suggest that age stereotypes influence technology use in late adulthood through complementary processes. Future studies should further explore these relationships by integrating both theoretical approaches. Interventions and policies promoting positive intergenerational contact and positive views on age and ageing should thus contribute to the digital inclusion of older adults.